PERLINDUNGAN HUKUM TERHADAP PARA PIHAK ANTARA PELAKU USAHA DAN KONSUMEN E-COMMERCE AKIBAT CEDERA JANJI (WANPRESTASI) - Hidayati (Fakultas Hukum Universitas Borobudur, 2023)
Internet usage in Indonesia is around 78.19 percent of the total number. The aim of this research is to legally protect business actors and consumers in order to develop their businesses through advances in internet technology to reduce costs, save time, and overcome problems related to physical contracts. The approach method used in this research is normative juridical, namely referring to applicable laws and regulations. Meanwhile, the normative approach is carried out by studying library materials or secondary data about legal principles and case studies as library legal research. The results of the research conclude that the regulations of the Republic of Indonesia Law Number 8 of 1999 concerning Consumer Protection, and Republic of Indonesia Law Number 7 of 2014 concerning Trade are also related to E-commerce which uses electronic transactions, explaining that every agreement made legally is also valid as law for which makes it so, if there is a form of default committed by each stakeholder online, there is a dispute so that legal action for compensation is required through the Consumer Dispute Resolution Agency which is tasked with handling and resolving disputes between both parties, supported by a legal umbrella to protect victims in E-commerce which refers to applicable laws and regulations.